Increasing the Corrosion Resistance of Metal Through the Application of Fillers Based on Nanochalk and Nanotalc in Paint and Varnish Materials in Shipbuilding and Aircraft Industry - Fatyanova , N.V. (Herald of Azerbaijan Engineering Academy, 2023)
The article examines the results of introducing a technology for increasing the corrosion resistance of metal in the shipbuilding and aircraft industry by adding chalk and talc nanopowders to fillers, as well as substantiating the rationality and economic efficiency of using chalk and talc nanoparticles in the production of paints and varnishes, discussing in detail the method of obtaining nanoparticles and the application of the obtained experimentally nanopowders for the preparation of a new type of enamel. Also, in connection with the trend towards ecologization, the article pays special attention to the environmental component of the production process, determines the degree of danger that the manufactured enamel poses to the environment and the human body.